Teaching of forensic odontology in basic dental programmes in nine Australian dental schools: A survey. (10th February 2019) - Soon, Alistair; Graham, Jeremy; Bassed, Richard
Abstract: Purpose: The aim of this survey was to determine whether forensic odontology forms part of the basic dental programme in the nine Australian dental schools, which aspects of forensic odontology were taught, and the barriers and issues that prevent forensic odontology being part of any dental curriculum. The survey also examines the teaching of cranio‐facial anatomy and dental record‐keeping, as these two subjects can play an important role in forensic odontology. Materials and methods: Study design and participants: A postal questionnaire survey on the teaching of forensic odontology was conducted between November 2016 and April 2017, being sent to the dean of school, head of school, or acting head of school, each representing the nine Australian dental schools. The paper questionnaire consisted of eight questions requesting information concerning whether or not the dental school has faculty staff who are registered forensic odontologists or registered general dentists with a forensic odontology postgraduate qualification, and how many hours of teaching (including lectures and practicals) were dedicated to cranio‐facial anatomy and dental record‐keeping. Results: Five out of nine dental schools replied to the questionnaire. This gives a response rate of 55.56%. Staff members: Four dental schools had at least one or more forensically trained staff members. Only one dental school did not have a staff member who is trained in forensic odontology. Cranio‐facial anatomy: Three out of the five dental schools responded that each of the cranio‐facial anatomy lecture and practical programmes were more than 16 hours each throughout the whole dental programme, whereas the other two dental schools responded that each of the lecture and practical programmes were between 7 and 11 hours. Dental record‐keeping: All five dental schools responded that the lecture hours dedicated to dental record‐keeping are between 1 and 6 hours throughout the whole dental programme. For the practical sessions, three out of the five dental schools responded that the hours dedicated are between 1 and 6 hours. Teaching of forensic odontology: Three out of the five dental schools responded that forensic odontology is taught as part of a dental subject in the dental programme, with the total hours dedicated to the teaching being between 1 and 6 hours, with teaching being delivered in the form of lectures only. Two of the five dental schools that did not teach forensic odontology as part of any dental subjects mentioned that the main reason for not teaching forensic odontology is due to lack of teaching time. Conclusion: This is the first Australian project investigating the teaching of forensic odontology in Australian dental schools. The authors found that three dental schools teach forensic odontology; however, it is limited to only 1 to 6 hours of teaching time. All five dental schools teach extensively into cranio‐facial anatomy and dental record‐keeping. However, as one of the recognised dental specialities in Australia, and the role it plays in justice, human rights and humanitarianism, all Australian dental schools should provide an opportunity for students to learn and be aware of forensic odontology as part of their training programmes, which include the importance of accurate dental records and its application to forensic odontology.